Reading Rabbinic Distinctions Between the Titles and Texts of the Psalms as Metaphors for Theological Framing Devices - Michal, Gavin (Journal for Semitics, 2025)
This article examines how subtle “textual framing” embedded within the presentation of all religious texts can influence the texts even before they are read. Using Psalms as a point of departure, 116 of the 150 psalms begin with introductory titles or superscriptions also known as paratexts, for example, “Lamenatzeach—For the Choirmaster.” Depending on the editions, these paratexts are often distinguished from the base or main text of the psalm by some form of spacing to indicate that they were not part of the original text. Their purpose is to frame the psalm for the reader. This study explores the Psalter’s paratexts as metaphors for the framing strategies adopted by various theological ideologies within their internal written, oral, and other formulations; and suggests a critical and conscious engagement with all “paratextual framing,” rather than an unmitigated acceptance thereof.
paid
Keywords: Jewish messianism; Midrash; Psalms; Talmud; paratext; superscriptions; theological framing